(untitled) (Annals of Medical Research, 2023)
Aim: NeuroD2 transcription factor is a key regulator of neurogenin-NeuroD signaling network and induces neuronal development, differentiation, neurogenesis and calcium dependent signaling. NeuroD2 regulates expression of survival and plasticity related proteins in neurons. Surprisingly, inhibition of NeuroD2 causes an increase in apoptotic cell death. Even though previous studies found out important data about NeuroD2 function, molecular interactions of NeuroD2 behind all of these impacts remains elusive. For this reason, it was aimed to shed light on the proteome profile of NeuroD2 based changes in the N2A cell line. Materials and Methods: NeuroD2 over-expression and NeuroD2 inhibition groups were constructed via lentiviral vectors. Mouse N2A cell line was transfected with the given vectors and incubated for 6 hours. After incubation samples were prepared for proteomic analyses with Filter Aided Sample Preparation (FASP) protocol and LC-MS/MS analysis was carried out. Results: Under conditions of overexpression and inhibition, detected proteins were filtered according to significant cut off values. The filtered proteins were further investigated to exhibit a coherent expression in each situation. Eventually, increased NeuroD2 activity was accompanied by an increase in N-alpha-acetyltransferase 25 (NAA25), and Synaptobrevin homolog (YKT6). On the other hand, when NeuroD2 was suppressed, expression of Cytoplasmic Dynein 1 Light Intermediate Chain 1, Kinesin-Like Protein (KIF-11), Leucine-tRNA Ligase (LARS1), and Ubiquitin-Associated Protein 2 (UBA2) were found to be upregulated with a reverse action. Conclusion: Up-regulations of the proteins Cytoplasmic Dynein 1, KIF11, LARS1, and UBA2 suggested that these proteins might be controlled by inhibition of NeuroD2. In this contex it can be said that, axonal transport, neuronal signaling, and activity of PI3K/AKT pathway can be indirectly regulated by NeuroD2.